Growth performance of broiler chickens fed low-protein diets with constant concentration of limiting amino acids under a closed-house environment - Akmal, Ainil Fatin; Idrus, Zulkifli; Soleimani Farjam, Abdoreza (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A study was conducted to determine the effect of feeding low-protein diets with constant concentration of lysine, methionine, threonine and trypthopan on the growth performance of broiler chickens raised in a closed-house environment. Feeding broilers low-protein diets reduced body weight (day 35) but not feed intake and feed conversion ratios (day 1-35).